The Concept of Bridal Chamber in the Valentinian Inscriptions - Kelmelytė, Gražina (Literatūra, 2020)
This article investigates the Valentinian ritual, called “bridal chamber”, in the only surviving Valentinian funeral epitaphs, Flavia Sophe and NCE 156. These inscriptions stand out from the context of other Valentinian sources because they are extant in the Ancient Greek, not the Coptic language. Bridal chamber is a polysemous concept in the Nag Hammadi texts, and therefore begs the question, what does it mean in the Valentinian funeral epitaphs? Furthermore, this article is an attempt to elucidate the connections between the two inscriptions by interpreting the concept of bridal chamber.